The Impact of Financial Technology on Bank Assurance: A Case Study in the Australian Insurance Market (International Journal of Financial, Administrative and Economic Sciences, 2026)
The current research aims to analyze the impact of financial technology (Fin Tech) on bank assurance, through a case study of the Australian market during the period (2020-2025). The importance of this research lies in its focus on measuring the relationship between Fin Tech indicators (represented by the number of ATMs and point-of-sale terminals) and bank assurance indicators (represented by credit life insurance premiums, death claim settlement ratios, and claims paid to premiums ratios). Data were analyzed using descriptive statistics, including the arithmetic mean, standard deviation, and coefficient of variation, in addition to using SPSS software (version 23) to perform linear regression analysis to test the validity of the hypothesis stating that there is a statistically significant effect of Fin Tech on bank assurance. The research reached several conclusions, the most important of which is the existence of a strong positive statistically significant relationship between the number of point-of-sale terminals and credit life insurance premiums.
Keywords: Financial Technology; Bank assurance; Credit Life Insurance; ATMs; Point of Sale; Australia